2000
DOI: 10.1038/81685
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome sequence variation and the history of human populations

Abstract: Binary polymorphisms associated with the non-recombining region of the human Y chromosome (NRY) preserve the paternal genetic legacy of our species that has persisted to the present, permitting inference of human evolution, population affinity and demographic history. We used denaturing high-performance liquid chromatography (DHPLC; ref. 2) to identify 160 of the 166 bi-allelic and 1 tri-allelic site that formed a parsimonious genealogy of 116 haplotypes, several of which display distinct population affinities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
719
10
12

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 885 publications
(788 citation statements)
references
References 20 publications
42
719
10
12
Order By: Relevance
“…This allows us to 'root' the tree and shows that the root falls closest to African populations. All of these findings, which are in accord with many other studies based on different types of genetic variation assessed in different samples of humans [25][26][27][28] , support an evolutionary scenario in which anatomically modern humans evolved first in Africa, accumulating genetic diversity. A small subset of the African population then left the continent, probably experienced a population bottleneck and founded anatomically modern human populations in the rest of the world 29 .…”
supporting
confidence: 89%
“…This allows us to 'root' the tree and shows that the root falls closest to African populations. All of these findings, which are in accord with many other studies based on different types of genetic variation assessed in different samples of humans [25][26][27][28] , support an evolutionary scenario in which anatomically modern humans evolved first in Africa, accumulating genetic diversity. A small subset of the African population then left the continent, probably experienced a population bottleneck and founded anatomically modern human populations in the rest of the world 29 .…”
supporting
confidence: 89%
“…A number of recent studies carried out in numerous populations have shown that most Y chromosomes can be classified into monophyletic units (haplogroups), which tend to be specific to each continent and major ethnic group [7][8][9]. This study takes advantage of this ethnic/geographic specificity to define better the origins and relationships of the populations living in the Western Mediterranean basin.…”
Section: Introductionmentioning
confidence: 97%
“…Studies of the geographical and ethnical structure of phylogeny lead to the well-known ''out-of-Africa'' hypothesis of modern human evolution and the subsequent peopling of the entire world. New binary markers allow for the construction of more robust genetic phylogenies than before (Underhill et al 1996;Hammer et al 1998;Karafet et al 1999;Su et al 1999Su et al , 2000Thomson et al 2000;Underhill et al 2000;Hammer et al 2001;Karafet et al 2001;Underhill et al 2001;Wells et al 2001;Lell et al 2002;Qamar et al 2002;Tajima et al 2002;Zerjal et al 2002).…”
Section: Introductionmentioning
confidence: 99%